Use of ranibizumab for the treatment of subretinal neovascularization in pathologic myopia: a prospective study - Blavatska, О.M.; Kustryn, T.B.; Korol, A.R. (Ukrainian Journal of Ophthalmology, 2026)
Purpose: To determine the efficacy of ranibizumab as a treatment for subretinal neovascularization (SRNV) in pathologic myopia. Materials and Methods: This was an uncontrolled, prospective cohort study, involving 66 pathologic myopic eyes (65 patients) with SRNV. Patients were treated with 0.05-mL (0.5 mg) intravitreal ranibizumab and followed up over 12 months. The best-corrected visual acuity (BCVA) at 12 months was used as a primary end point. Safety, OCT retinal thickness at the fovea, activity of SRNV as assessed by fluorescein angiography, and the number of ranibizumab injections were secondary end points. Results: Compared with baseline, the visual acuity improved significantly at all follow-up points (р = 0.001). The mean BCVA was 0.2 (SD 0.13) at baseline and improved to 0.4 (SD 0.21) at month 12. The mean CRT was 313 µm (SD 82) at baseline and decreased to 244 µm (SD 31) at the end point (р = 0.0001). Conclusions: Intravitreal ranibizumab was found to be a safe and efficacious treatment for SRNV in pathologic myopia at the follow-up of 12 months. In routine clinical practice, the use of ranibizumab for the treatment of SRNV in pathologic myopia results in a statistically significant improvement in visual acuity and a regression in retinal edema.